Ethnomathematics in elementary education: A systematic review of pedagogical approaches, technological innovation, and global implementations - Jeinne Mumu; Rully Charitas Indra Prahmana; Benidiktus Tanujaya (Universitas Hamzanwadi, 2026)
Ethnomathematics, which integrates mathematical practices grounded in cultural traditions, has gained prominence as an approach to fostering culturally responsive learning in elementary mathematics education. This systematic review synthesizes 65 peer-reviewed empirical studies published between 2020 and 2025, examining its implementation across diverse global contexts. The analysis is organized around three domains: pedagogical approaches incorporating local narratives, cultural artifacts, and Indigenous knowledge; technological innovations, including digital modules, augmented reality, and mobile learning platforms; and comparative curricular frameworks across countries such as Indonesia, Brazil, Thailand, the United States, Mexico, Zimbabwe, Nigeria, Israel, and the Middle East. These contexts were selected based on their representation in the reviewed literature and relevance to the study’s focus. Findings indicate that culturally grounded instruction enhances student engagement, problem-solving, and mathematical literacy, often with moderate to large effect sizes. Technology integration expands access and relevance, though digital inequities persist. Cross-national variation is evident. Key challenges include limited authentic resources, fragmented teacher development, and lack of standardized assessment. Future research should prioritize longitudinal studies and AI-supported learning environments.